2020
DOI: 10.1515/med-2020-0017
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of recombinant heparin-binding hemagglutinin adhesin protein in spinal tuberculosis

Abstract: AbstractBackground and aimTo explore the diagnostic value of recombinant heparin-binding hemagglutinin adhesin (HBHA) protein antigen in spinal tuberculosis.Materials and methodsForty patients with spinal tuberculosis were included in the experimental group and 40 healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…(Gonzalez‐Carrillo et al, 2016). Several studies indicated that both Ag85 complex encoded by fbpA/B/C and hbhA‐ encoding heparin‐binding haemagglutinin A (HBHA) are important adhesions of Mycobacteria (Pu et al, 2020; Viljoen et al, 2020), Lap protein encoded by lap is an adhesion molecule on the surface of Listeria (Jaradat & Bhunia, 2002), and the ibeA‐ encoding IbeA protein is an invasion of meningitic Escherichia coli (Damodara et al, 2008). However, except for gapA and mec gene family, the pathogenic effect of the predicted genes encoding adhesion and invasion in N. seriolae infection still need to be further verified.…”
Section: Discussionmentioning
confidence: 99%
“…(Gonzalez‐Carrillo et al, 2016). Several studies indicated that both Ag85 complex encoded by fbpA/B/C and hbhA‐ encoding heparin‐binding haemagglutinin A (HBHA) are important adhesions of Mycobacteria (Pu et al, 2020; Viljoen et al, 2020), Lap protein encoded by lap is an adhesion molecule on the surface of Listeria (Jaradat & Bhunia, 2002), and the ibeA‐ encoding IbeA protein is an invasion of meningitic Escherichia coli (Damodara et al, 2008). However, except for gapA and mec gene family, the pathogenic effect of the predicted genes encoding adhesion and invasion in N. seriolae infection still need to be further verified.…”
Section: Discussionmentioning
confidence: 99%
“…Heparin-binding haemagglutinin adhesin (HBHA), a surface-exposed TB protein, is one of the adhesins of M. tb, whose expression can be used as an indicator for PTB [146]. More so, HBHA has been reported to induce overproduction of IFN-γ in latent TB patients [147,148].…”
Section: Blood-associated Tb Biomarkersmentioning
confidence: 99%